Estudio traslacional sobre los mecanismos fisiopatológicos de la hipertensión arterial en la menopausia - Zilberman, Judith Miriam (2016)
This is a translational study of the physiopathological mechanisms of hypertension\nand CVD in menopausal women from the experimental aspect and its correlation\nwith the clinical aspects.\nAims: the aims of this study is to evaluate the effects of enalapril on: hormonal axis,\nBP, endothelial function in normotensive and hypertensive menopausal women and\nin menopause and hypertension experimental models: hormone receptors, oxidative\nstress, NO system, renal and cardiac remodelling, vascular and tissue fibrosis.\nA study in 1034 women showed a relationship between hypertension, dyslipidaemia,\nhyperglycaemia, and obesity.\nIn 29 menopausal women (normotensive and hypertensive) enalapril increased the\nlevels of estradiol decreasing the menopausal symptoms.\nThe evaluation of the endothelial function in 498 women showed that hypertension\nand menopause cause an early increase in vascular stiffness index.\nIn menopausal SHR rats enalapril caused a decrease in heart weight, left ventricle\nweight and the diameter of the myocytes. In kidneys, left ventricle, and aorta there\nwas an increase in the NOS activity, there was an improvement in peroxidation,\nfibrosis with an increase in the a (alpha) estrogen receptors expression in the medulla and\nß (beta) estrogen receptors expression in the cortex and heart.\nThese experimental and clinical trials show that translational research may be\nuseful in human healthcare.